Concept of cross – city rail route in Wrocław to create the LRT system - Mariusz Korzeń (Przegląd Komunikacyjny)
Abstract: The article presents a proposal for the construction of a cross-city rail route in Wrocław in order to create a LRT system. The main motivation for the creation of the LRT system is the constantly growing traffic towards the center caused by the increasing number of people living in the peripheral parts of the city and neighboring municipalities making up the Wrocław agglomeration. As an example of an efficient LRT system using a cross-city tunel is the S-Bahn system in Munich was cited, in which the railway tunnel running through the city center determines large flows of passengers and is therefore one of the main means of transport in the entire agglomeration. In the next part, the current state of the Wrocław Railway Junction is briefly discussed, thus showing the city's great potential to create the LRT system. Places where direct access to the railway network should be provided have been indicated. It was proposed to create two cross-diameter routes running entirely from the tunnel. Their course should be dictated by the location of the traffic generators indicated in the article in the center of Wrocław. In the summary, the author presents the benefits of building new routes and mentions the need for the development of the rail transport network resulting from the Wrocław Mobility Policy. The creation of a new route running through the city center would significantly increase the transport attractiveness of the railways, and thus, the new route would be a key element for the creation of an efficiently functioning LRT system in the city and the entire Wrocław agglomeration. Keywords: Railway tunel; Cross – city route; Agglomeration railway; Wrocław